Prevalence and predictors of waterpipe smoking cessation among young adults in the US: Findings from a population-based study. (December 2022) - Gautam, Prem; Sharma, Eva; Li, Tan; Maziak, Wasim
Highlights: During 2013–2019, 25.1% of the young adult waterpipe smokers quit smoking. Tobacco smoking restriction at home promotes waterpipe smoking cessation. Waterpipe smokers who regret are more likely to quit than who do not. Co-use of waterpipe and alcohol hinders cessation. Abstract: Background: The prevalence of waterpipe tobacco (WPT) smoking is 9.2 % among young adults aged 18–24 years in the United State (US). Adequate understanding of the factors predicting WPT smoking cessation among the young population is essential to tobacco control efforts. This study assessed the prevalence and predictors of WPT smoking cessation among young adults. Methods: The population assessment of tobacco and health (PATH) study data (waves 1–5) was used for the study. A total sample of 561 young adults exclusively using WPT (past 30-days) was used for the analysis. The probability of WPT smoking cessation (no use in the past 12 months) was estimated using the Kaplan-Meier survival method, and the predictors were assessed using the Cox proportional hazards regression model. Results: During the five waves, 25.1 % of the young adult WPT smokers quit smoking. Among them, 58.2 % were females and the remaining 41.8 % were males. The Hispanics (40.2 %) had the highest rate of cessation among the ethnic groups. Regret smoking (adjusted hazard ratio (aHR) = 2.33, 95 % confidence interval (CI) = 1.24–4.36), smoking restriction at home (aHR = 2.86, 95 % CI = 1.41–5.88), and living in Midwest geographical region (aHR = 2.11, 95 % CI = 1.16–3.84) increased the likelihood whereas alcohol use (aHR = 0.62, 95 % CI = 0.41–0.93) decreased the likelihood of cessation among the young adult WPT smokers. Conclusions: Communicating the health and economic consequences associated with WPT smoking (e.g., pictorial health warning labels), involving smoker's household members in WPT awareness campaigns, and closing regulatory loopholes related to WPT venues will increase the WPT smoking cessation rate among the young population in the US.